Implementasi Extreme Programming untuk Sistem Jasa Pemesanan Design Website dan UI/UX - Ramadhan Abelio Nusa Putra; Rezki Kurniati; Eva Yumami (STIKes Ibnu Sina Ajibarang, 2024)
In this study, a website and UI/UX design ordering service system was developed. This system offers clients to make orders through a website that can make it easier for people to find service experts in the field of website and UI/UX design. The development of this system was carried out using the Extreme Programming (XP) method, this method is a software development that emphasizes flexibility, communication, and adaptability to changing requirements. Researchers will use short iterations to create, build, and test websites and UI/UX designs. To ensure a thorough understanding of client requests and preferences, developers and customers will communicate more frequently. The testing method on the system used in this study is User Acceptance Testing, which is a testing stage where the system or software is evaluated to ensure that the system meets user needs and requirements. Users perform this test to ensure that the system functions properly and meets their expectations. The results of this study, system development using the Extreme Programming (XP) method is very helpful for developers because the needs of each user are clearly defined, the use of the User Acceptance Testing method shows that each function of the application system operates according to user needs. Thus, the use of the Extreme Programming method can improve the system development.